I repertori dei movimenti ecclesiali: Studio di alcuni casi (De Musica, 2022)
The present contribution moves from general considerations on the educational value of music and on the characteristics of sacred music in order to offer some reflections on the relationship between liturgical music and mystagogy, on the reasons for the need for this relationship, on its requirements, what it implies and what are its expected objectives. We will deal with the repertoires of some significant ecclesial movements both for their consolidated structure and for the large number of adherents. They are structured groups with their own program and statutes, approved by the Catholic Church, which have acknowledged, each with their own peculiarities and differentiations, the need to reconcile liturgical music and mystagogy in their own itinerary of faith. We will take a closer look at their repertoires, and we will make some considerations on them. We will also take into account those repertoires which are not a direct expression of movements, but are widely used in parishes and communities, sometimes used by the same movements together with their own ones.
Keywords: Actuosa participatio; Ecclesial movements; Liturgical music; Mystagogy.